NUTRITION EDUCATION VIDEO IMPROVES BODY IMAGE PERCEPTION AND EATING PATTERNS OF STUDENTS OF SMA NEGERI 2 TABANAN - I Putu Suiraoka; Kadek Septine Melina Dewi; Ni Made Yuni Gumala (Proceeding B-ICON, 2023)
Body image is a person’s subjective concept of his own physique. The nutritional status of adolescents is influenced by various factors, namely the perception of body image, eating patterns and other factors. The purpose of this study was to determine the effect of providing nutritional education videos through the Telegram application on the body image and eating patterns of female students at state Senior High School 2 Tabanan. This type of research is quasi-experimental with a one group pretest-posttest design. The sample size in this study is 69 samples. Variables were collected by interview method with body image and eating pattern questionnaire form SQ-FFQ. Data is presented with a frequency table and then analyzed using the Wilcoxon test. The results showed that before and after the intervention there were 56 samples (81.2%) and 26 samples (37.7%) had negative body image. Before and after the intervention there were 36 samples (52.2%) and 49 samples (71.0) with good eating types. Before and after the intervention there were 39 samples (56.5%) and 23 samples (33.3%) with less eating frequency. For the total intake of macronutrients, the results of data processing were obtained in the less/deficit category. The statistical test results stated that there was an effect of providing educational videos on body image with a p value of 0.000 (<0.05). Based on diet (type, frequency and amount) with all p values (<0.05) it was stated that there was an effect of giving educational videos on eating patterns.